Impact of dermatologic adverse events induced by targeted therapies on quality of life. (May 2016) - Charles, Cécile; Bungener, Catherine; Razavi, Darius; Mateus, Christine; Routier, Emilie; Lanoy, Emilie; Verschoore, Michèle; Robert, Caroline; Dauchy, Sarah
Abstract: Background: Investigations about the impact of dermatologic adverse events on quality of life in the context of targeted therapies are quite recent and results vary in some dimensions. This article aims to summarize the existing data and to clarify needs in terms of clinical management and future research. Methods: A literature review was done with Pubmed, Medline, Scopus and PsycInfo databases and it combined the empirical studies published in English and in French over the past ten years. Results and conclusions: Dermatologic adverse events globally have a low to moderate impact on quality of life, mainly in the physical and emotional domains. Reasons for inter-individual variations in adjustment and long-term impact are still not well known. Making quality of life assessments systematic, making early referrals of patients to dermatology consultations and giving more attention to individual experience were identified as measures that could help prevent deterioration in quality of life.